Serum endotoxins and flagellin and risk of colorectal cancer in the european prospective investigation into cancer and nutrition (epic) cohort - Kong, S; Tran, H; Gewirtz, A; McKeown-Eyssen, G; Fedirko, V; Romieu, I; Tjønneland, A; Olsen, A; Overvad, K; Boutron-Ruault, M; Bastide, N; Affret, A; et al. (American Association for Cancer Research, 2016)
Background: Chronic inflammation and oxidative stress are thought to be involved in colorectal cancer development. These processes may contribute to leakage of bacterial products, such as lipopolysaccharide (LPS) and flagellin, across the gut barrier. The objective of this study, nested within a prospective cohort, was to examine associations between circulating LPS and flagellin serum antibody levels and colorectal cancer risk. Methods: A total of 1,065 incident colorectal cancer cases (colon, n = 667; rectal, n = 398) were matched (1:1) to control subjects. Serum flagellin- and LPS-specific IgA and IgG levels were quantitated by ELISA. Multivariable conditional logistic regression models were used to calculate ORs and 95% confidence intervals (CI), adjusting for multiple relevant confouding factors. Results: Overall, elevated anti-LPS and anti-flagellin biomarker levels were not associated with colorectal cancer risk. After testing potential interactions by various factors relevant for colorectal cancer risk and anti-LPS and anti-flagellin, sex was identified as a statistically significant interaction factor (Pinteraction < 0.05 for all the biomarkers). Analyses stratified by sex showed a statistically significant positive colorectal cancer risk association for men (fully-adjusted OR for highest vs. lowest quartile for total anti-LPS + flagellin, 1.66; 95% CI, 1.10–2.51; Ptrend, 0.049), whereas a borderline statistically significant inverse association was observed for women (fully-adjusted OR, 0.70; 95% CI, 0.47–1.02; Ptrend, 0.18). Conclusion: In this prospective study on European populations, we found bacterial exposure levels to be positively associated to colorectal cancer risk among men, whereas in women, a possible inverse association may exist. Impact: Further studies are warranted to better clarify these preliminary observations. Cancer Epidemiol Biomarkers Prev; 25(2); 291–301. ©2016 AACR.